From Boardrooms to Bedrooms: Unveiling Workplace Extramarital Affairs - Siti Syahbanu; Muhammad Irfan Syaebani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the impact of power dynamics, gender roles, and organizational structures on extramarital affairs within professional environments. It examines how hierarchical structures and societal conventions influence relationships, frequently to the detriment of women. This research employs interdisciplinary approaches, including Marxist alienation, power-approach theory, and social identity theory, to link workplace infidelity to broader concerns of gender inequity, and corporate accountability. The study seeks to examine the influence of organizational hierarchies on workplace relationships, the significance of cultural notions such as "ibuism" and "neo-ibuism" within Indonesian society, and the psychological and professional ramifications of these dynamics. It also assesses business policies and human resources initiatives in the management of workplace relationships. A desk research analysis method is employed, examining literature from sociology, psychology, and management disciplines. Secondary data from international research offer insights into workplace infidelity and gender discrepancies. Principal themes encompass power and gender dynamics, workplace hierarchies, cultural expectations, and human resource regulations pertaining to workplace relationships. The study emphasizes the influence of authority and control on relationships, frequently resulting in exploitation, harassment, and professional stagnation for women. This study enhances gender equity, and corporate governance by promoting regulations that guarantee equitable and secure professional environments. It advocates for a decentralized, decolonized, and gender-sensitive approach to workplace relations, highlighting the necessity for ethical business frameworks that avert exploitation and foster diversity and equality.